Dramaturgi Politikus Perempuan Pariaman Di Parlemen Dalam Perspektif Ulama Di Propinsi Sumbar - Akdila Bulanov; Penmardianto; Muhammad Taufik; Muhammad Azamul Haq (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to analyze the dramatization of female politicians in Pariaman, West Sumatra Province, focusing on the perspective of ulama regarding their roles and contributions to local politics. Using a descriptive qualitative approach, this research explores how female politicians construct their image and identity on the political stage, as well as the challenges and support they encounter within the context of local cultural and religious norms and values. Data were collected through in-depth interviews with several female politicians in the parliament, along with ulama who hold influence in the community. The findings indicate that female politicians in Pariaman utilize communication strategies that reflect Islamic values to gain legitimacy from the public. The support from ulama plays a crucial role in shaping public perception of women's involvement in politics, positively influencing societal acceptance. The study also identifies various challenges faced, including gender stigma, patriarchal norms, and structural barriers that limit the political participation of female politicians. These findings provide new insights into the interaction between gender, religion, and politics in West Sumatra, as well as the importance of dialogue between female politicians and ulama in fostering stronger support for women's roles. This research is expected to serve as a reference for policies and programs that encourage increased political participation of women at the local level, contributing to the development of gender studies within the context of Indonesian politics.